DIGITALIZATION OF AGRICULTURAL SECTOR MANAGEMENT: NEW APPROACHES AND SOLUTIONS - Осмятченко, Володимир; Музиченко, Тетяна (SWorldJournal, 2025)
The relevance of this study is driven by the urgent need for the transformation of the agricultural sector within the framework of the digital economy. As agriculture faces increasing pressures from climate change, resource scarcity, and global food secur